2022
DOI: 10.3389/fbioe.2022.818572
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Fat Extract Prevents Tail Suspension–Induced Bone Loss by Inhibiting Osteocyte Apoptosis

Abstract: Introduction: As the space field has developed and our population ages, people engaged in space travel and those on prolonged bed rest are at increasing risk for bone loss and fractures. Disuse osteoporosis occurs frequently in these instances, for which the currently available anti-osteoporosis agents are far from satisfactory and have undesirable side effects. CEFFE is a cell-free fraction isolated from nanofat that is enriched with a variety of growth factors, and we aim to investigate its potential therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…6 ). Moreover, the effect of CEFFE on proliferation was reported in a study of skin repair, and an anti-apoptotic effect was reported in osteoporosis, which was consistent with our findings [ 18 , 35 ]. In addition to its effect on proliferation and apoptosis, CEFFE can also enhance the mitochondrial function of GCs.…”
Section: Discussionsupporting
confidence: 92%
“…6 ). Moreover, the effect of CEFFE on proliferation was reported in a study of skin repair, and an anti-apoptotic effect was reported in osteoporosis, which was consistent with our findings [ 18 , 35 ]. In addition to its effect on proliferation and apoptosis, CEFFE can also enhance the mitochondrial function of GCs.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, recombinant irisin (R-irisin), cell-free fat extract, and injection of cyclic mechanical stretch-treated bone mesenchymal stem cell-derived exosomes (CMS) had protective effects on the bones [ 58 , 59 , 64 , 69 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strontium ranelate is already used in OP treatment, where it showed a significant increase in BMD on PMP OP [ 126 , 127 ]. The injection of cell-free fat extract also has a positive effect on BL, because it alleviates the HLU-induced decrease in BV/TV, trabecular number, and cortical thickness [ 69 ]. Furthermore, the injection of CMS in mice exposed to HLU increased BMD, BV/TV, cortical thickness, and trabecular thickness and number, while reducing the number of OCs [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al . demonstrated that CEFFE prevents osteocyte apoptosis in a tail-suspension mouse model by attenuating ROS production [13]. Yin et al .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of CEFFE on the bone microarchitecture was evaluated in accordance with our previously published study [13]. Briefly, right tibias and vertebral bodies were harvested for high-resolution μCT analysis (μCT 80, Scanco, Zurich, Switzerland) at a resolution of 10 μm per voxel, 70 kV voltage, and 114 μA electric current.…”
Section: Methodsmentioning
confidence: 99%